Mobile Vaccination Teams for Improving Vaccination Coverage in the Kyrgyz Republic: Results of a National Health System-Strengthening Project during the First Two Years of the COVID-19 Pandemic - Kubanychbek Monolbaev; Alyia Kosbayeva; Marzia Lazzerini (MDPI AG, 2023)
(1) Background: This implementation study reports on the results of the mobile vaccination teams' (MVTs) activities during the first two years of the COVID-19 pandemic in Kyrgyzstan, when other vaccination services were disrupted. (2) Methods: Through a national health system-strengthening project under an order of the Ministry of Health, in 2020, the number of MVTs was increased, focusing on internal immigrant settlements around the cities of Bishkek and Osh and geographically remote areas. MVTs provided free vaccination services. (3) Results: MVTs vaccinated a total of 125,289 and 158,047 children in 2020 and 2021, respectively. The higher contribution of MVTs to vaccination coverage was in children under 5 years of age, with the three top vaccines being IPV (8.9%), MMR (7%), and PCV (6.6%). In 2021, 13,000 children who had not received an IPV vaccination and 8692 children who had not received the Pentavalent vaccine (DPT-HBV-Hib) were reached. The number of cases of vaccine-preventable disease reported in official statistics has reduced over time. (4) Conclusions: MVTs increased vaccination coverage in Kyrgyzstan, in particular in remote regions and migrant settlements, where it accounted for a considerable proportion of the vaccinated. This study adds to previous evidence in the literature of the role of MVTs as a strategy to improve immunization in hard-to-reach populations, particularly children.